Evaluation of expiratory capacity with severe asthma following bronchial thermoplasty. Issue 1 (26th November 2018) - Ishii, Satoru; Iikura, Motoyasu; Shimoda, Yukiko; Izumi, Shinyu; Hojo, Masayuki; Sugiyama, Haruhito
Abstract : Bronchial thermoplasty (BT) is a bronchoscopic treatment to reduce the amount of smooth muscle in the bronchial wall in patients with severe asthma. Reducing smooth muscle in the airway wall reportedly alleviates air trapping and decreases expiratory volume. In the current study, expiratory computed tomography (CT) was performed in 10 patients who underwent BT at our facility, and their expiratory volume was evaluated. We observed an improvement in the expiratory volume on CT in nine of the 10 patients. Total expiratory lung volume decreased from 1693 ± 907 to 1426 ± 853 mL, indicating an improvement of approximately 15%. Use of CT for evaluation of expiratory volume may be a method for assessing the effectiveness of BT. Abstract : Bronchial thermoplasty (BT) is a bronchoscopic treatment for severe asthma using thermal energy to reduce the amount of smooth muscle in the bronchial wall. In the present study, expiratory computed tomography (CT) imaging was performed before and after BT, and changes in expiratory lung capacity were measured. Use of CT for evaluation of expiratory volume may be a method for assessing the effectiveness of BT.